Bronchoalveolar lavage of ventilator‐associated pneumonia patients for antibiotic resistance and susceptibility test. Issue 1 (6th January 2022) - Ahmadinejad, Mojtaba; Mohammadzadeh, Sanaz; Pak, Haleh; Hashemiyazdi, Seyedehhamideh; Soltanian, Ali; Rahimi, Mahsa; Ahmadinejad, Izadmehr
Abstract: Background and Aims: Ventilator‐associated pneumonia is highly prevalent nosocomial infection among patients under mechanical ventilation. Bronchoalveolar lavage (BAL) is effective in identifying the type of pathogen involved and determine the course of antibiotic. The aim of this study was to evaluate the prevalence of different pathogens involved in ventilator‐associated pneumonia (VAP) and associated antibiotic resistance and sensitivity pattern. Methods: In this descriptive cross‐sectional study, patients admitted to the intensive care unit under mechanical ventilation at Shahid Madani Educational and Medical Center in Karaj during 2018 and 2020 were included. BAL samples were obtained from the patients. Demographic data, duration of hospitalization, duration of mechanical ventilation, and antibiotic susceptibility and resistance tests were recorded for all the patients. Results: Among 335 patients included in the study, 215 (64.2%) were males. The mean age of the patients was 55.06 ± 14.90 years. The most common pathogens reported were Acinetobacter baumannii (40%), Pseudomonas aeruginosa (21.2%), and Staphylococcus aureus (13.4%). The mean age of the patients, gender, duration of mechanical ventilation, and duration of hospitalization were not associated with the type of pathogen, P > .05, respectively. Conclusion: BAL of these patients indicated that various pathogens are responsible for VAP, and can vary from patient to patient. Antibiotic resistance and susceptibility pattern of these pathogens vary and therefore is important in determining the course of the treatment.